Clinical and biological features of paediatric acute myeloid leukaemia (AML) with primary induction failure in the Japanese Paediatric Leukaemia/Lymphoma Study Group AML‐05 study. (19th February 2019) - Miyamura, Takako; Moritake, Hiroshi; Nakayama, Hideki; Tanaka, Shiro; Tomizawa, Daisuke; Shiba, Norio; Saito, Akiko M.; Tawa, Akio; Shimada, Akira; Iwamoto, Shotaro; Hayashi, Yasuhide; Koike, Takashi; et al.
Summary: The prognosis of paediatric acute myeloid leukaemia (AML) with primary induction failure (PIF) is extremely poor, and effective treatment strategies have not been established. We investigated the clinical and biological features of paediatric AML patients with PIF registered to the Japanese Paediatric Leukaemia/Lymphoma Study Group AML‐05 study. The 3‐year overall survival rate of the 41 PIF patients was 19.0%. High leucocyte count, M7 morphology, and unfavourable genetic aberrations, such as FLT3 ‐internal tandem duplication, NUP98‐NSD1 and high MECOM or PRDM16 expression, were risk factors for PIF. More effective treatment strategies based on leukaemia biology need to be urgently explored.